2006
DOI: 10.1002/ardp.200600034
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Chalcones and Analogues as Hypolipidemic Agents

Abstract: In order to evaluate the anti-hyperlipidemic effect of synthetic chalcones and some analogues, nineteen compounds with different substituents in both rings were synthesized and hypolipidemic activities were measured in vivo using Triton WR1339 acute and hypercaloric chronic assays. 49,4-dichlorochalcone, 39,49,4-trichlorochalcone, and 49-chlorochalcone gave an excellent decrease in serum total cholesterol and triglycerides in the acute assay. These compounds also showed significant anti-lipidemic activity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…In support of this, Santos et al reported that chalcone compounds had significant anti-lipidemic activity. 55) In summary, the present study demonstrated that S. flavescens and its components, kurarinol and kuraridinol, had hypolipidemic effects in poloxamer 407-induced hyperlipidemic rats, where the compounds significantly lowered serum TC, TG, and LDL-C concentrations, elevated HDL-C levels, and decreased serum A.I. values.…”
Section: Discussionsupporting
confidence: 53%
“…In support of this, Santos et al reported that chalcone compounds had significant anti-lipidemic activity. 55) In summary, the present study demonstrated that S. flavescens and its components, kurarinol and kuraridinol, had hypolipidemic effects in poloxamer 407-induced hyperlipidemic rats, where the compounds significantly lowered serum TC, TG, and LDL-C concentrations, elevated HDL-C levels, and decreased serum A.I. values.…”
Section: Discussionsupporting
confidence: 53%
“…Fluvastatin ( 25 ), compound with indole moiety, was the first synthetic 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor (statin) and is used in the management of dyslipidemia in the primary and secondary prevention of cardiovascular disease [ 69 , 70 ]. In addition, a recent literature survey revealed that chalcone derivatives, such as 4′,4-dichlorochalcone ( 26 ), exhibited potential hypolipidemic activities [ 71 ]. Fibrates are selective agonists of the peroxisome proliferator-activated receptor gamma (PPARγ).…”
Section: Design Of New Chalcone Derivativesmentioning
confidence: 99%
“…An increase of triglycerides was observed in free chalcone-treated animals, while the encapsulation of R13 and R15 avoided these effects. Chalcones also induced a decrease in total cholesterol that could be related to a hypolipidemic effect of chalcones, as demonstrated in another study [ 36 ].…”
Section: Resultsmentioning
confidence: 62%